The effect of Afrocentric missense variations on the structural dynamics of CYP2B6 - Govender, Shaylyn Ashley (Rhodes University, Faculty of Science, Biotechnology Innovation Centre)
Cytochrome P450s are a superfamily of enzymes with over 50 members involved in metabolizing 90% of xenobiotics. Among the these, families 1, 2, and 3 are responsible for approximately 80% of clinical drug metabolism. This study investigates the effect of Afrocentric missense variants on the structural dynamics of CYP2B6. Molecular dynamic simulations reveal that specific variants affect the enzyme's flexibility and stability, potentially altering catalytic activity and drug binding properties. These findings highlight the importance of considering genetic variants in personalized medicine and drug development. By investigating CYP2B6's function and structural changes induced by missense variants, this research advances our understanding of the enzyme's role in drug metabolism. The study utilized computational tools such as GROMACS and AMBER for pre- and post-simulation analysis, with clustering and DSSP used to assess protein structures. Variants I328T, K282R, P428T and R140Q exhibited significant deviations in enzyme dynamics, while other variants caused minor shifts. Overall, the findings provide insight into the relationship between genetic variants and enzyme function, contributing to bioinformatics and molecular modelling approaches in drug discovery. Future studies could explore the structural and fuctional impacts of CYP2B6 bound to substrates such as antimalarials, expanding the investigation to a broader range of missense variants.
Keywords: CYP2B6; Structural dynamics; Metabolism; Missense mutation; Molecular dynamics